Residual rectal mucosa after stapled vs. handsewn ileal J-pouch-anal anastomosis in patients with familial adenomatous polyposis coli (FAP) - a critical issue - Ganschow, Petra; Treiber, Irmgard; Hinz, Ulf; Leowardi-Bauer, Christine; Büchler, Markus W.; Kadmon, Martina (Langenbeck's archives of surgery, 2015)
Restorative proctocolectomy has become the standard surgical procedure for familial adenomatous polyposis (FAP) patients. The use of stapler devices has initiated a controversial discussion concerning the ileal pouch-anal reconstruction. Some authors advocate a handsewn anastomosis after transanal mucosectomy. A double-stapled anastomosis leads to better functional results but seems to bear a higher risk of residual rectal mucosa with dysplasia and adenomas. The present study systematically analyses the rate of residual rectal mucosa after restorative proctocolectomy and handsewn vs. stapled anastomosis.